The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1590/1516-3180.2020.0602.r1.0402021
|View full text |Cite
|
Sign up to set email alerts
|

Can physical activity levels and relationships with energy expenditure change the clinical aspects of sarcopenia and perceptions of falls among elderly women? Observational cross-sectional study

Abstract: A sedentary lifestyle is the primary risk factor for muscle weakness. 1 Sarcopenia, defined as the loss of muscle mass and function, affects quality of life and increases the risk of physical limitations and disability among older adults. 1,2 Currently, epidemiological statistics show that sarcopenia affects about 50% of elderly people, depending on the country, ethnicity of the patient, diagnostic criteria and healthcare setting. [1][2][3][4] Overall, the prevalence among men is about 25% and among women, 20%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 46 publications
0
3
0
1
Order By: Relevance
“…This can be explained by 46.2% of older adults reported physical activity twice or more of week. Several studies have shown that physical activity is associated with a lower prevalence of sarcopenia (25)(26)(27)(28)(29). A study conducted among Japanese communitybased older adults demonstrated that 7% were sarcopenic by AWGS criteria (30).…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…This can be explained by 46.2% of older adults reported physical activity twice or more of week. Several studies have shown that physical activity is associated with a lower prevalence of sarcopenia (25)(26)(27)(28)(29). A study conducted among Japanese communitybased older adults demonstrated that 7% were sarcopenic by AWGS criteria (30).…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…Some evidences revealed that high PA indicated higher muscle mass, muscle strength and better physical performance compared with low and moderate PA levels [ 52 , 53 ]. But others did not suggest such association [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sarcopenia is a progressive and widespread age-related skeletal muscle disorder that increases the risk of disability, falls, and fall related injuries and increases hospitalization and mortality rates for patients [5]. The global pandemic of sarcopenia, skeletal muscle loss, and weakness, which prevails in up to 50% of older adults, is increasing worldwide due to the expansion of aging populations (especially if they are older than 80, frail and inactive), there is a strong relationship between nutrition [6], exercise [7] and sarcopenia. The MNA is a Mini Nutrition Scale specifically designed to evaluate the nutritional status of older adults, which includes anthropometric measurements, a holistic assessment, a dietary questionnaire, and a subjective assessment [8].…”
Section: Introductionmentioning
confidence: 99%